Якість вищої освіти: від минулого до сучасного - Біляковська, Ольга (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The article deals with concept of “quality of education” in its historical aspect, such a basic concept as “quality” is outlined and main approaches to interpreting this concept are highlighted. It is noted that quality of education reflects the development of the system of education and society of a certain period and changes within some time according to the demands of the society, individual and state. Key characteristics of higher education are emphasized and indicators of its quality are defined. Ensuring quality of education is a multifaceted task on the way of integration of the Ukrainian system of education into the European educational space.
Keywords: quality; quality of education; quality of higher education; indicators of quality